Modified delivery of SAPIEN 3 valve in the pulmonary position: Evolution of technique or dire need?. Issue 3 (8th November 2018) - Shahanavaz, Shabana; Rockefeller, Toby; Nicolas, Ramzi; Balzer, David
Abstract: Transcatheter pulmonary valve replacement (TPVR) is now common practice in patients with significant pulmonary regurgitation (PR), stenosis (PS), or mixed pulmonary valve disease. While the Melody valve (Medtronic, Inc.) and its delivery system were specifically designed for use in the right ventricular outflow tract (RVOT), Sapien valves (XT and S3, Edwards Lifesciences, Inc.) and their delivery systems (Novaflex and Commander) were not. As a result, placement of Sapien valves in the RVOT can be challenging secondary to the stiffness of the current delivery system. Manipulating a stiff delivery system within the RV also introduces risk to the tricuspid valve and its chordal attachments. We report a novel delivery technique for the Sapien S3 valve which has greatly simplified valve delivery into the RVOT and may potentially reduce the risk of tricuspid valve injury.